Breaking the Spell of Regulatory Competition: Reframing the Problem of Regulatory Exit - Henri Tjiong (Max-Planck-Projektgruppe Recht der Gemeinschaftsgüter, 2000)
Regulatory competition is increasingly becoming the dominant argument on regulatory structure in both the debate on federalism in the United States and that on subsidiarity in the European Union. The argument, briefly put, is that regulatory competition might produce efficiency benefits that justify yielding federal or harmonized regulation in favor of decentralizing governance. The present direction in this debate is to identify in which contexts and under what circumstances these efficiency benefits are likely. This paper intends to contribute to this debate by analyzing the proposition that regulatory competition can be understood as an argument of regulatory structure modeled on the principles of market order. The purpose of this paper is to clarify but ultimately to challenge the wisdom of this intriguing argument. Regulatory competition is an intriguing and sophisticated argument which, as it deals with interpreting the complex dynamic between political and economic integration, deserves to be spelled out in full and with considerable care. The persuasive force of regulatory competition as an academic proposition however lies in the double efficiency argument hidden in it. Regulatory competition can be and is most often understood as a macro-argument for federal governance structures in that these allow for extrinsic efficiency benefits in the form of experimentation and innovation at a broad scale (economies of scope). But regulatory competition can also be framed as a force for improving the intrinsic efficiency of regulations by allowing actors to structure their need for economic coordination to their own liking, thus incorporating the preferences of consumers into the structure of regulation (a micro argument). The debate in the US after several critiques which expressed frustration at the broadness and inexactness of the initial macro arguments has steadily moved on to focus on the micro argument which attempts to detail the instances and conditions under which regulatory competition might indeed work to improve the intrinsic efficiency of regulation. Regulatory competition, to the extent that actors internalize the costs of their decision, has come to be viewed as a largely untapped mechanism for improving the efficiency of rules in a potentially wide range of legal domains.
Keywords: 340